Inheritance of consonant phonemes from Proto-Austronesian language into Acehnese: A comparative historical linguistic study - Dardanila, Dardanila; Widayati, Dwi; Gustianingsih, Gustianingsih; Harahap, Nur Hayati (Indonesian Journal of Applied Linguistics, 2024)
Acehnese is a member of the Austronesian language family. As a descendant language, it retains significant vocabulary from Proto-Austronesian, while some vocabulary has evolved uniquely in Acehnese. In Comparative Historical Linguistics, such inheritance is termed linear inheritance, the direct preservation of phonemes from the ancestor language to the descendant language without significant change; and innovative inheritance, phonological modifications that occur as languages evolve over time. Despite the abundant of studies on Austronesian languages, there is only small portions discussing the preservation of specific consonant phonemes from Proto-Austronesian in its descendant languages. This study describes the inheritance of Proto-Austronesian consonant phonemes in Acehnese. It aims to contribute to the development of Comparative Historical Linguistics. In order to track the transmission of consonant phonemes from Proto-Austronesian to Acehnese, the study used the Comparative Historical approach. It is anticipated that this method will reveal patterns of phonological innovation and retention. By examining the evolution of consonant phonemes, this study reveals the mechanisms shaping the Acehnese language and offers insights into the historical phonology of Austronesian languages. It used a list of 200 Swadesh vocabulary items to demonstrate that many Proto-Austronesian consonant phonemes are inherited linearly in Acehnese (e.g., *b → b, *c → c, *d → d), while others show innovative changes (e.g., *p → t, *s → h). Our knowledge of the preservation of consonant phonemes during the history of Austronesian languages is anticipated to grow as a result of this work. Furthermore, it is anticipated that this research would shed light on certain linguistic mechanisms, such as phonological innovation and retention, that have shaped Acehnese's evolution as a descendant language. The study's findings also provide insights into more comprehensive language theories that differentiate between inventive and linear inheritance. These results give a framework for examining the phonological evolution of additional Austronesian languages, in addition to advancing the reconstruction of Proto-Austronesian phonology.